2020
DOI: 10.1177/1759720x20946220
|View full text |Cite
|
Sign up to set email alerts
|

Reduced skeletal muscle independently predicts 1-year aggravated joint destruction in patients with rheumatoid arthritis

Abstract: Background: Numerous cross-sectional studies have reported the associations between rheumatoid arthritis (RA) and reduced skeletal muscle. We firstly explored the dynamic change of skeletal muscle and its effect on RA clinical outcomes in a real-world prospective cohort. Methods: Consecutive RA patients were treated according to the treat-to-target strategy and completed at least 1-year follow up. Clinical data and muscle index (assessed by bioelectric impedance analysis) were collected at baseline and visits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…2 In ammation and Immune Mediated Diseases Laboratory of Anhui Province, 81 Meishan Road, Hefei, Anhui, China. 3 Center for Genetic Epidemiology and Genomics, School of Public Health, Soochow University Medical College, Suzhou, China. 4 Department of Rheumatology and Immunology, the First A liated Hospital of Anhui Medical University, 218 Jixi Road, Hefei, Anhui, China.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In ammation and Immune Mediated Diseases Laboratory of Anhui Province, 81 Meishan Road, Hefei, Anhui, China. 3 Center for Genetic Epidemiology and Genomics, School of Public Health, Soochow University Medical College, Suzhou, China. 4 Department of Rheumatology and Immunology, the First A liated Hospital of Anhui Medical University, 218 Jixi Road, Hefei, Anhui, China.…”
Section: Fundingmentioning
confidence: 99%
“…RA appears mostly in women and may occur at any age, with a peak incidence between 50 and 60 years old [1]. In general, progressive disability and shortened life expectancy are almost universal in RA patients [2], furthermore, physical pain also seriously affects the quality of life [3]. The exact pathogenesis of RA is not yet known [4], but it is believed that environmental, genetic, and infectious factors may interact in susceptible individuals and the heritability of RA is approximately 65% [5].…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous observational studies have reported that almost 36%-55% of patients with rheumatoid arthritis have myopenia (i.e. low skeletal muscle mass), [5][6][7] and approximately 29%-38% have sarcopenia. 7,8 In addition, an incidence of myopenia has been reported as high as 9.3% over one year follow up for patients with rheumatoid arthritis who initially were not classified as myopenia.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, an incidence of myopenia has been reported as high as 9.3% over one year follow up for patients with rheumatoid arthritis who initially were not classified as myopenia. 6 Older adult patients with sarcopenia tend to have greater physical difficulty relative to their peers without sarcopenia; 2,9 this phenomenon is also present in patients with rheumatoid arthritis. 5,10,11 In recent research on the relationship between skeletal muscle mass and disability in rheumatoid arthritis, low muscle mass was significantly associated with a severe disability score.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has long been regarded as a marker of acute in ammation, recent studies have shown that CRP also plays an important regulatory role in a variety of chronic in ammatory related diseases [19,20]. It has long been recognized that elevated serum CRP correlates positively with RA severity and progression, and systemic CRP level is signi cantly increased in OA patients [21,22].…”
Section: Introductionmentioning
confidence: 99%